Eficácia de um gel com reduzida concentração de fluoreto suplementado com hexametafosfato de sódio sobre o processo de desmineralização do esmalte dentário: estudo in vitro - Miyasaki, Marcela Lumi [UNESP] (2014)
The objective of this study was to evaluate the in vitro effect of low-fluoride (F) gels supplemented with hexametaphosphate (HMP) on enamel demineralization. Materials and methods: Bovine enamel blocks (n = 120) were selected based on surface hardness (SH) and divided into six treatment groups (n = 20 per group: a) gel Placebo, b) 9%HMP, c) 4,500 μg F/g d 4,500 μg F/g + 9% HMP, e) 9,000 μg F/g and f) 12,300 μg F/g (Acid gel). Blocks were treated with respective gels only once. Ten blocks of each group were anylized about formed CaF2 concentration. The other ten blocks were subjected to five pH cycling (pH 4,7-6h and pH 7,0-18h) during seven days. After the pH cycling, it was determined the final hardness surface (SH1) to calculate the percentage of loss surface hardness (%SH) and then, the concentration the CaF2 e F (retained).The results were subjected to ANOVA followed by Student-Newman-Keuls test (p < 0.05). Results: The groups 4500 9%HMP, 9000 and Acid showed lower %SH, the lowest values ΔKHN were found for the 4500 9%HMP and Acid gel (p > 0.05). The gel acid group showed higher concentrations the CaF2 formed when compared to the other groups (p <0,05). After all cycles of pH, the group 4500 9% HMP and acid gel showed similar concentrations the CaF2 retained (p > 0,05). The concentration the F formed was similar the groups 4,500, 4,500 + 9% HMP, 9,000 and acid gel (p>0,05). There was no chance in the concentration the F retained after all cycles of pH these groups. Conclusion: It is possible to inhibit enamel demineralization with low-F gels supplementing these gels with 9% HMP. Clinical relevance: The low-F gel containing HMP can be regarded as a safer alternative for clinical use from...